Determinants of UITM Johor students’ behavioral intention to use e-learning system - Abd Aziz, Nurul Aien Binti; Bin Musa, Mohd Hafizan; Ghul, Zahirah Binti Hamid; Abd Aziz, Noreen Noor Binti; Khalid, Rusnani Binti Mohamad (International Journal of Engineering and Technology, 2018)
Recently,there are many universities in Malaysia including local and private implemented and developed an e-learning system for various purpose. Along with the era of using technology, many universities take this opportunity to further develop the e-learning system for using by students as well as an educator. Hence, this research aims to investigate the relationship between Perceived ease of use, perceived Usefulness, Attitude, E-learning self-efficacy and behavioral intention to use e-learning .The structural model was developed based on Technology Acceptance Model (TAM).223 respondents comprising of UiTM Johor students as a user of e-learning system participated in this survey. Simple random sampling technique was used to measure the Perceived ease of use, perceived Usefulness, Attitude, E-learning self-efficacy and behavioral intention to use e-learning. Pearson correlation was used to measure the relationship between the variables. The results indicate significant relationship between all the independent variable (Perceived ease of use, perceived Usefulness, Attitude, E-learning self-efficacy) with the dependant variable (behavioral intention to use e-learning).Findings from the study would be beneficial to university especially for UiTM and relevant department to keep maintain the system as well as to ensure the system is fully utilized by student and educator as an educational platform.Â